2016
DOI: 10.1002/ijc.30023
|View full text |Cite
|
Sign up to set email alerts
|

The proportion cured of patients diagnosed with Stage III–IV cutaneous malignant melanoma in Sweden 1990–2007: A population‐based study

Abstract: The survival in cutaneous malignant melanoma (CMM) is highly dependent on the stage of the disease. Stage III-IV CMM patients are at high risk of relapse with a heterogeneous outcome, but not all experience excess mortality due to their disease. This group is referred to as the cure proportion representing the proportion of patients who experience the same mortality rate as the general population. The aim of this study was to estimate the cure proportion of patients diagnosed with Stage III-IV CMM in Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Women with locoregional metastases had somewhat lower risk of later developing distant metastases than men independent of age. A previous study on patients with stage III at primary diagnosis also showed heterogenic survival outcome between men and women . For patients with distant metastases, M1c (65%) was the dominating site which could be compared to AJCC data (stage IV at primary diagnosis) where the proportion of M1c was 58% …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Women with locoregional metastases had somewhat lower risk of later developing distant metastases than men independent of age. A previous study on patients with stage III at primary diagnosis also showed heterogenic survival outcome between men and women . For patients with distant metastases, M1c (65%) was the dominating site which could be compared to AJCC data (stage IV at primary diagnosis) where the proportion of M1c was 58% …”
Section: Discussionmentioning
confidence: 84%
“…A previous study on patients with stage III at primary diagnosis also showed heterogenic survival outcome between men and women. 19 For patients with distant metastases, M1c (65%) was the dominating site which could be compared to AJCC data (stage IV at primary diagnosis) where the proportion of M1c was 58%. 3 In the present study, 37.6% of the patients with recurrences developed distant metastases without previous locoregional metastases indicating haematogenous metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Each risk factor (period of diagnosis, age, sex and WCC) was included in a univariable model and a fully adjusted model including all the covariates. The cure model provides estimates separately for each combination of covariates in the model, therefore to make comparisons between levels of each covariate while adjusting for the others we calculated standardised estimates (Andersson et al , ; Eriksson et al , ). For example, the cure proportion for each sex was estimated assuming that the distribution of the other covariates (age, period of diagnosis and WCC) was the same as the whole study population.…”
Section: Methodsmentioning
confidence: 99%
“…In Sweden it is the fifth most prevalent malignant neoplasm both in men (following prostate, colon, non-melanocytic skin and urinary tract tumors) and women (following breast, colon, non-melanocytic skin and uterine neoplasms) with an annual incidence of 5% [3, 4]. …”
Section: Introductionmentioning
confidence: 99%